2016
DOI: 10.1371/journal.pone.0150963
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Gene Expression Differences between Lymphangiogenic and Non-Lymphangiogenic Non-Small Cell Lung Cancer Cell Lines

Abstract: It is well established that lung tumors induce the formation of lymphatic vessels. However, the molecular mechanisms controlling tumor lymphangiogenesis in lung cancer have not been fully delineated. In the present study, we identify a panel of non-small cell lung cancer (NSCLC) cell lines that induce lymphangiogenesis and use genome-wide mRNA expression to characterize the molecular mechanisms regulating tumor lymphangiogenesis. We show that Calu-1, H1993, HCC461, HCC827, and H2122 NSCLC cell lines form tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Therefore, biomarkers that can help to predict prevalence of lymph node metastasis may be helpful for the clinical evaluation. VEGF-C, a subtype of VEGF family, has been reported to participate in the lymphatic metastasis of various solid tumors including ovarian cancers (Bednarek et al 2008;Wu et al 2012;Regan et al 2016;Wang et al 2016). Interestingly, our study revealed that the mRNA expression of VEGF-C was positively correlated with TBL1XR1 levels in clinical tumor tissues.…”
Section: Discussionsupporting
confidence: 44%
“…Therefore, biomarkers that can help to predict prevalence of lymph node metastasis may be helpful for the clinical evaluation. VEGF-C, a subtype of VEGF family, has been reported to participate in the lymphatic metastasis of various solid tumors including ovarian cancers (Bednarek et al 2008;Wu et al 2012;Regan et al 2016;Wang et al 2016). Interestingly, our study revealed that the mRNA expression of VEGF-C was positively correlated with TBL1XR1 levels in clinical tumor tissues.…”
Section: Discussionsupporting
confidence: 44%
“…Despite expectations, none of the analyzed genes, except DSP, was activated in tumor tissue. Moreover, in malignant tissues, a statistically significant decrease in transcript level was observed for growth factors VEGFC and VEGFD and their receptor VEGFR3 that are thought to be the most potent inductors of lymphatic vessel formation (10,34,35), and transcripts for lymphatics-specific markers LYVE1 (36,37) and FOXC2 (38). The expression levels of other well-estimated lymphatic molecules PDPN (39,40) and PROX1 (41,42) were similar to those in nonmalignant tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer has been among the earliest and most intensely studied diseases using microarray platforms [39]. Two very recent studies have used microarray technologies to derive a robust prognostic gene expression signature for early stage lung adenocarcinoma [40] and identify a 17 gene expression signature that distinguishes lymphangiogenic from non-lymphangiogenic NSCLC cell lines [41]. Molecular signatures help to reveal the biologic spectrum of lung cancers, throw light on the pathogenetic alterations in gene expressions and cellular pathways, identify prognostic and predictive gene signatures, customize therapies, identify new therapeutic targets and evaluate new drugs [39].…”
Section: Discussionmentioning
confidence: 99%